A qualitative approach on the main causes of human resource churning - Olga Alexandra Chinita Pirrolas (2022)
Introduction: Despite the relevance of the operationalization of the concept of human resource churning, this is still an underdeveloped theme, with little literature and empirical studies. It is in this sense that arises the interest in studying this theme, allowing to contribute to the development of a subject of great complexity, as well as to contribute to both the increase of literature and empirical studies. Goals/ Methods: This article aims to analyze through a qualitative approach, what are the main causes of human resource churning. The study follows a qualitative approach using the analysis of international literature and 20 semi-structured interviews as instruments of data collection. As a form of data treatment, content analysis was used to select the main variables under study. Results: Through the data obtained it was possible to define as main causes of churning: low salary; lack of career progression; lack of individual development; rigid schedules; weak leadership; competition; locality; bad work environment; weak organizational culture; lack of promotion; lack of recognition; lack of availability; difficulty in work-family conciliation and lack of motivation. Conclusions: As a way to minimize the occurrence of churning, it is proposed that organizations implement strategic measures in order to meet the needs and expectations of their workers so that they feel satisfied and motivated in the organization and with their work, preventing the decision to leave the organization.